Development of a Fast and Sensitive Method for the Determination of As(Iii) at Trace Levels in Urine by Differential Pulse Anodic Voltammetry Using a Simple Graphene Screen–Printed Electrode - Segura-Segura, R; Segura-Segura, R (Elsevier Inc., 2020)
A simple and fast anodic voltammetric method was employed to determine traces of As(III) in urine samples using commercial screen–printed graphene electrodes without subsequent modification. To obtain a sensitive and selective method for As(III) determination, the effects of various parameters such as pH, supporting electrolyte concentration, accumulation potential (Eacc), accumulation time (tacc), and potential scan conditions were studied. The optimum experimental conditions were chosen to be as follows: pH of 2.8 (0.01 mol L−1 phosphate buffer), scan increment of 4 mV, pulse width of 80 ms, pulse period of 0.5 s, and pulse amplitude of 200 mV. Differential pulse voltammograms were obtained by scanning from −0.80 V to 0.80 V without applying an accumulation step. Under these conditions, one peak was observed at 0.27 V due to As0 oxidation. After optimizing the experimental conditions, the anodic peak current for As was found to be linearly related to its concentration up to ca. 5.0 μg L−1, with detection and quantitation limits (DLs, QLs) of 0.28 µg L−1 and 0.92 µg L−1, respectively. The developed method was validated by the determination of As(III) in spiked tap water from our laboratory, which showed an As(III) concentration of 50.64 ± 0.10 μg L−1 (spiked with 50.0 μg L−1); two urine samples (where As was not detected) spiked with As(III) 0.73 μg L−1 and 0.91 μg L−1 (in the cell) showed an As(III) concentration of 0.70 μg L−1 and 0.91 μg L−1, respectively. The method was successfully applied to the determination of Astotal in 16 urine samples obtained from workers occupationally exposed to inorganic arsenic compounds without previous treatment. The results obtained for Astotal were compared with measurements made by an external analytical laboratory, which used HG–AAS. To determine Astotal, As(V) was reduced in the presence of thiosulfate in an acid medium. The electrode showed good stability and repeatability. © 2020 Elsevier B.V.